IEEE International Symposium on Electromagnetic Compatibility
DOI: 10.1109/isemc.1990.252790
|View full text |Cite
|
Sign up to set email alerts
|

A technique of electromagnetic interference measurements with high-impedance electric and low-impedance magnetic fields inside a TEM cell

Abstract: Transverse electromagnetic (TEM) cells are usually used to perform electromagnetic interference (EMI) measurements of equipment inside the cell in a plane wave-field environment. This paper describes a new technique of generating predominantly highimpedance electric or low-impedance magnetic fields inside a TEM cell for EM1 measurements of relatively small size printed circuit boards (PCBs), electronic devices, etc. The technique simulates environments similar to the near-field EM1 environment for intrasystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The authors of [2] varied the load impedance of a TEM cell to obtain various known field strengths and wave impedances inside a TEM cell. The authors of [3] [4] excited the TEM cell at both ports using sinusoidal waveforms. This paper introduces a technique where arbitrary timedomain signals drive the TEM cell at both ends.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [2] varied the load impedance of a TEM cell to obtain various known field strengths and wave impedances inside a TEM cell. The authors of [3] [4] excited the TEM cell at both ports using sinusoidal waveforms. This paper introduces a technique where arbitrary timedomain signals drive the TEM cell at both ends.…”
Section: Introductionmentioning
confidence: 99%
“…Imaida et al and Wang et al, in order to study the effects of in vivo near-field exposure on rodent brain and liver carcinogenesis, have used especially designed 'exposure boxes' to reproduce the cellular telephones [10,11]. Another study to simulate a near-field EMI environment was reported by Das et al where they fed the in-phase and out-of-phase signals into both ports of the TEM cell [12]. None of these efforts, however, utilized commercially available cellular phones as the sources of EM exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The SPW has broadband characteristics compared with the DPW. However, the DPW can provide a dominant H-field (wave impedance 0 ) and a dominant E-field (wave impedance ) [9]- [11]. Recently, the authors proposed a bent coupled transmission-line (BCTL) cell whose inner conductors are bent in the tapered section [12].…”
Section: Introductionmentioning
confidence: 99%